A Meta-Analysis of Association Between Strabismus in Children/Adolescents and Risk of Mental Health Disorders - Krungkraipetch L; Krungkraipetch N; Threetong T (Clinical Ophthalmology)
Luksanaporn Krungkraipetch,1 Naruporn Krungkraipetch,2 Thanatporn Threetong1 1Department of Ophthalmology, Faculty of Medicine, Burapha University, Chonburi, Thailand; 2Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Thanatporn Threetong, Department of Ophthalmology, Faculty of Medicine, Burapha University, 169 Long-Had Bangsaen Road, Bang Saen Subdistrict, Mueang Chonburi District, Chonburi, 20131, Thailand, Email Thanatporn@go.buu.ac.thBackground: Strabismus, or eye misalignment, is a common condition in children and adolescents. This meta-analysis examined the association between strabismus and mental health disorders including attention deficit hyperactivity disorder (ADHD), anxiety, depression. The strength and consistency of the relationships between strabismus and the risk of mental health disorders and how the associations vary according to characteristics including study size, temporal trends, and type of strabismus type were assessed.Methods: We conducted a meta-analysis with nine observational studies published between 2008 and 2024, involving 683,942 participants. The effect sizes were calculated as odds ratios (ORs) with 95% confidence intervals (CIs), and heterogeneity was assessed using the I² statistic to determine the associations between strabismus and mental health disorders.Results: The analyses revealed a significant positive association between strabismus and mental health disorders, with a weighted average OR of 1.92 (95% CI: 1.38– 2.66; I² = 99.7%). Temporal trends suggested that earlier studies reported larger effect sizes, whereas more recent studies showed modest although significant associations. The strongest associations were observed in studies of exotropia; the ORs ranged from 1.44 to 2.70. The study sizes and precisions varied; larger studies provided more reliable estimates and smaller studies showed wider CIs.Conclusion: Strabismus was significantly associated with an increased risk of ADHD, anxiety, and depression. This association was consistent across different strabismus types and study designs. These findings underscore the importance of mental health screening in children and adolescents with strabismus, particularly those with exotropia. Further research should explore the mechanisms underlying this relationship and the effects of early intervention programs.Keywords: exotropia, esotropia, attention deficit hyperactivity disorder, anxiety, depression